1997
DOI: 10.1038/nm1297-1369
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of CCR5 and CXCR4 on human Langerhans cells and macrophages: Implications for HIV primary infection

Abstract: Transmission of HIV-1 is predominantly restricted to macrophage (Mphi)-tropic strains. Langerhans cells (LCs) in mucosal epithelium, as well as macrophages located in the submucosal tissues, may be initial targets for HIV-1. This study was designed to determine whether restricted transmission of HIV-1 correlates with expression and function of HIV-1 co-receptors on LCs and macrophages. Using polyclonal rabbit IgGs specific for the HIV co-receptors cytokines CXCR4 and CCR5, we found that freshly isolated epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
227
1
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(250 citation statements)
references
References 36 publications
19
227
1
3
Order By: Relevance
“…CCR5 ϩ immature DC (iDC) differentiated from CD34 ϩ HPC, or freshly isolated from the skin, have been shown to express low to undetectable membrane CXCR4 and to selectively replicate R5 viruses (8,34,35). Maturation induced by short-term culture of epidermal LC, or by adding monocyte-conditioned medium (MCM) or trimeric CD40 ligand (CD40LT) to in vitro differentiated DC, results in decreased CCR5 expression and CXCR4 up-regulation, but increased permissivity to both X4 and R5 strains (8,34). However, at variance with CD4 ϩ T lymphocytes (36) that require activation signals to complete HIV reverse transcription and support virus replication, virus production appears 10-to 100-fold lower in mDC than in iDC (34,35).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…CCR5 ϩ immature DC (iDC) differentiated from CD34 ϩ HPC, or freshly isolated from the skin, have been shown to express low to undetectable membrane CXCR4 and to selectively replicate R5 viruses (8,34,35). Maturation induced by short-term culture of epidermal LC, or by adding monocyte-conditioned medium (MCM) or trimeric CD40 ligand (CD40LT) to in vitro differentiated DC, results in decreased CCR5 expression and CXCR4 up-regulation, but increased permissivity to both X4 and R5 strains (8,34). However, at variance with CD4 ϩ T lymphocytes (36) that require activation signals to complete HIV reverse transcription and support virus replication, virus production appears 10-to 100-fold lower in mDC than in iDC (34,35).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Although they do not express DC-SIGN, LCs express CD4 and HIV chemokine coreceptors, and these molecules have been shown to mediate infection of LCs (11)(12)(13)(14). Immature LCs express surface CCR5, but not surface CXCR4, immediately after isolation from skin; CCR5 on LCs also mediates fusion with cells expressing the HIV envelope protein gp120 (11). Likewise, Patterson et al (15) examined human cervix and found that CCR5 mRNA expression was at least 10-fold higher than CXCR4 mRNA expression in this tissue.…”
mentioning
confidence: 99%
“…CD11c ϩve and CD11c Ϫve blood DCs, Langerhans cells (LCs), and in vitro-derived monocytederived DCs (MDDCs) all express CD4 and CCR5 and can be productively infected in vitro. [8][9][10][11][12] However, HIV also bound several DC populations independently of CD4. 8,13,14 The heavy glycosylation of gp120 with mannose and fucose saccharides suggested HIV bound to cells also via lectin receptors.…”
mentioning
confidence: 99%